Stem cells : scientific facts and fiction - Mummery, Christine...[et al] (Elsevier, 2011)
Recent advances in the fields of medicine and technology have led to the development of stem cell therapy. A stem cell is a cell that has the potential to develop into many different types of cell in the body. It has the ability to divide and copy itself and at least one other specialized type of cell.